Animation of electronic and optical processes in semiconductors - Yeo, Raymond Chin Keong. (2009)
Semiconductor fundamental is an important subject in school of electrical and electronic engineering. It explains the properties of semiconductor and how semiconductor actually works. Without having a clear picture of how semiconductor works, it could result in the misunderstanding of the working principle and application of semiconductor devices.